Development of Learning Tools with Project-Based Learning (PjBL) Model on Students' Creative Thinking Skills in Renewable Energy Material - Lindang Agus Siyamuningsih; Nur Khoiri; Harto Nuroso; Muhammad Syaipul Hayat (Postgraduate, University of Mataram, 2025)
This study aims to develop learning devices with a project-based learning model in order to improve students' creative thinking skills in physics subjects on renewable energy material. This type of research is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMAN 1 Semarang with the research subjects being a physics teacher and 10th grade students. The research instruments consist of three types, including 1). Feasibility test using a questionnaire sheet, 2). Practicality test using observation sheets and questionnaires, and 3). Effectiveness test using creative thinking skills questions on renewable energy material. Research data related to the effectiveness test in the form of pre-test and post-test were analyzed using the N-gain test. Based on the data analysis, the results obtained include 1). The results of the validation of the learning devices with an average percentage value of 79% (high), 2). The results of the physics teacher's response regarding the practicality of the learning devices obtained a percentage of 83% (very practical), and 3). The results of the effectiveness test using the N-gain test showed that there was an increase in students' creative thinking skills on the renewable energy material taught using the project-based learning (PjBL) model learning device. So it can be concluded that the use of project-based learning models can improve students' creative thinking skills in studying material about renewable energy.